Integrating Digital Entrepreneurship and Economic Education to Enhance Entrepreneurial Competence and Business Innovation among University Students - Yuli Astini; Baiq Desthania Prathama; Dedy Febry Rachman; Syaiful Amri (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
The digital economy requires universities to develop students’ entrepreneurial competence and business innovation through economic and digital entrepreneurship education. This study examines the effects of economic education and digital entrepreneurship on entrepreneurial competence and business innovation, with entrepreneurial competence as a mediating variable. Using a quantitative explanatory design, data were collected from 340 students in economics-, business-, management-, and economics education-related programs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that economic education and digital entrepreneurship significantly affect entrepreneurial competence (b = 0.515, p 0.001; b = 0.450, p 0.001). Entrepreneurial competence and digital entrepreneurship significantly affect business innovation (b = 0.557, p 0.001; b = 0.390, p 0.001), while economic education has no significant direct effect (b = -0.015, p = 0.695). Entrepreneurial competence also mediates both relationships. The findings suggest that universities should integrate economic education, digital entrepreneurship, and competence-based learning to strengthen student business innovation.